The Effect of Organizational Justice and Perceptions of Support on Performance through Organizational Citizenship Behavior (OCB) on Teacher Performance Appraisal (PKG) Employees in Malalayang District, Manado - Helta Magrita Kalalo; Ludi Wishnu Wardhana; Sutomo Sutomo (International Journal of Economics, Commerce, and Management, 2025)
Optimal performance of teacher performance appraisers (PKG) is a significant challenge in improving the quality of education in Malalayang District, Manado. The main problem that arises is the low perception of organizational justice and institutional support that influence the performance of these employees. This study aims to analyze the influence of organizational justice and perceived support on the performance of PKG employees through the mediation of Organizational Citizenship Behavior (OCB). The method used is quantitative with an associative design, involving 92 employees as a sample taken proportionally from a population of 119 PKG employees. Data were collected using a questionnaire and analyzed using Structural Equation Modeling Partial Least Square (SEM-PLS) techniques. The results showed that organizational justice and perceived support significantly influence OCB and performance, and OCB proved to be a mediator that strengthens the relationship. These findings indicate that improving organizational citizenship behavior can be an effective strategy in improving employee performance that impacts the quality of teacher assessment. The practical implications of this study suggest the need to strengthen fair organizational policies and provide optimal support to create a conducive work environment that supports the performance of PKG employees.